Academic Quality Assessment of the Faculty of Science Departments at the University of Tobruk Using the Weighted Linear Combination Model (WLC) (المجلة الدولية للبحوث العلمية, 2026)
​This study evaluates the academic and administrative quality of the Faculty of Science departments at the University of Tobruk using the Weighted Linear Combination (WLC) model. The assessment relied on three main, weighted indicators: Academic Competence (E) at 0.35, Teaching Effectiveness (A) at 0.40, and Stakeholder Satisfaction (S) at 0.25. Data were collected using standardized questionnaires and official department quality reports from the University of Tobruk. The weights were rigorously justified through a modified Delphi method and the Analytic Hierarchy Process (AHP). Findings reveal variation in quality levels among departments, with three rated as "Good" and five rated as "Very Good." The overall faculty quality score reached 76.7%, qualifying the faculty for institutional accreditation for a period of three years. The study confirms the WLC model's effectiveness as an objective and transparent tool for continuous quality monitoring and policy-making in Libyan higher education.